Lean production, work intensification and employee wellbeing: Can line-manager support make a difference?. (February 2022) - Huo, Meng-Long; Boxall, Peter; Cheung, Gordon W.
Using a two-wave survey of 315 workers in a lean manufacturing plant, this study examines how work intensification affects employee wellbeing and how its effects may be ameliorated. It demonstrates that work intensification is transmitted into poorer wellbeing through greater emotional exhaustion. It shows that this mediation process is moderated by line-manager support, which buffers the relationship between emotional exhaustion and wellbeing. The study suggests that the health-impairing risks of high work intensity in lean settings can be reduced through better supervisory support. Ensuring that line managers have the opportunity, skills and motivation to offer good support to workers is a vital aspect of the interventions needed to counteract the health risks posed by lean production.